Broadband tunable hybridized metamaterials absorber at terahertz regime. (19th May 2018) - Yue, Wang; Xin, Liu; Chao, Zhang Wen; Qian, Liu; Ying, Zhang; Shou, Mei Jin
ABSTRACT: We propose an improved design and numerical study of an optically tunable metamaterial absorber incorporated with photoconductive semiconductor based on an electric-field coupled inductor-capacitor resonator on the polyimide substrate in the terahertz regime. A blueshift of the resonance absorption frequency under photoexcitation can be demonstrated and a broadband tuning range on the order of 92% has been obtained. Without photoexcitation, we demonstrate the metamaterial with an absorptivity of 94% at resonance frequency ω0 = 1.02 THz. For conductivity of silicon σSi = 4 × 10 3 S/cm, the resonance keeps shifting to the higher frequency and the absorptivity of metamaterial is 98.9% at ω1 = 1.95 THz, and that of absorber drops to 14.9% at ω0 = 0.94 THz. This artificial hybridized metamaterial will play a key role in the construction of new THz devices to fill the so-called "THz gap".